HUBUNGAN PEMBERIAN MAKANAN PRELAKTEAL TERHADAP KEJADIAN SAKIT PADA NEONATUS - Dermawan Harahap; Ganis Indriati; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Neonates are newborns up to 4 weeks of age (0-28 days). The neonatal period is the period most susceptible to infection because the immunity of the neonate is still immature. At this time neonates need to be given breast milk (colostrum) which is high in antibodies, antiinfective and immunoglobulins to maintain their health, but prelacteal feeding can inhibit colostrum breastfeeding in neonates, this can increase the risk of infectious diseases such as ARI, fever and diarrhea. This study aimed to determine the relationship of prelacteal feeding to the incidence of pain in neonates. This study uses a research design description of correlation with aapproach retrospective and a sample of 45 neonates. The measuring instrument used is a questionnaire. The analysis used is univariate analysis to determine the frequency distribution and bivariate using the alternative Fisher Exact Test. The results of the study found that of 23 people (51.1%) respondents who were given prelacteal food, 5 (21.7%) of them experienced pain and obtained a p value of 0.049 with α 0.05 (p value <α) so that it can be concluded that there was a significant relationship between prelacteal feeding on the incidence of pain in the neonate. The results of this study can be a motivation for mothers who have a neonate to give exclusive breastfeeding and avoid prelacteal feeding, and to health workers, especially nurses at the health center to promote the exclusive breastfeeding of neonates.Keywords : Incidence of illness, neonates, prelacteal